Partisipasi Gen Z dalam Konteks Dinamika Pembangunan di Indonesia - Adittiya Putra Nur Hakim; Sally Sabela; Muhammad Faiqi Tsaqib; Ayu Wardani (Jurnal Penelitian Sosial Ilmu Komunikasi, 2024)
Generasi Z, also known as Gen Z, is set to play a pivotal role in shaping the future economy. Within the realm of developmental communication, Gen Z holds significant importance in disseminating information and raising awareness about humanitarian issues, environmental concerns, and sustainable economic development. This research aims to map out and elucidate the role of Gen Z in enhancing Indonesia's economy within the framework of participatory developmental communication theory. The study adopts a qualitative descriptive research approach. The findings reveal that Gen Z fulfills several crucial roles in developmental communication to bolster the economy, create job opportunities, and maximize the creative economic industries and startups. This aligns with the concept of participatory developmental communication, wherein Gen Z possesses immense potential to drive social change and engage in campaigns aimed at advancing development. Gen Z serves as change agents tasked with steering economic transformations towards a better future, fostering collective prosperity.